Volume 2: Combustion, Fuels and Emissions, Parts a and B 2010
DOI: 10.1115/gt2010-23498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combustor Inlet Geometry on Acoustic Signature and Flow Field Behavior of the Low Swirl Injector

Abstract: Low Swirl Injector (LSI) technology is a lean premixed combustion method that is being developed for fuel-flexible gas turbines. The objective of this study is to characterize the fuel effects and influences of combustor geometry on the LSI’s overall acoustic signatures and flowfields. The experiments consist of 24 flames at atmospheric condition with bulk flows ranging between 10 and 18 m/s. The flames burn CH4 (at φ = 0.6 & 0.7) and a blend of 90% H2 - 10% CH4 by volume (at φ = 0.35 & 0.4). Two combu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The mean velocity, U/Uo, in the inner region (r/R,, < 0.6) is less than the velocity through the outer region (r/R" > 0.6). The turbulence intensity u'/Uo is relatively uniform in the inner region, around 10%, but increases to 40% around r/R" = 1, indicating the presence of a shear layer at the bumer rim [26].…”
Section: Resultsmentioning
confidence: 99%
“…The mean velocity, U/Uo, in the inner region (r/R,, < 0.6) is less than the velocity through the outer region (r/R" > 0.6). The turbulence intensity u'/Uo is relatively uniform in the inner region, around 10%, but increases to 40% around r/R" = 1, indicating the presence of a shear layer at the bumer rim [26].…”
Section: Resultsmentioning
confidence: 99%
“…The vane shape did not affect the swirling flow appreciably but the curved-vane LSI had a much lower pressure drop [12]. The interaction of the recirculation zone and shear layer with both hydrocarbon and high-hydrogen content flames has been observed to form noticeable acoustic effects which can lead to severe combustion instabilities [13]. It has been identified that vortex shedding from the nozzle rim to be a major contributor to the acoustics [13].…”
Section: Introductionmentioning
confidence: 99%
“…Heat losses to the chamber walls are also known to alter the structure of the reacting flow [11,12]. A central bluff-body [2,13,14] and a diffuser [2,4,13,[15][16][17] constitute other widely used elements to enhance the stabilization of swirling flames. In high power systems, it is, however, more suitable to operate without any central insert to reduce the thermal stress on the solid components of the injector.…”
Section: Introductionmentioning
confidence: 99%